Pulmonary inflammatory effects of source-oriented particulate matter from California's San Joaquin Valley. (October 2015) - Plummer, Laurel E.; Carosino, Christopher M.; Bein, Keith J.; Zhao, Yongjing; Willits, Neil; Smiley-Jewell, Suzette; Wexler, Anthony S.; Pinkerton, Kent E.
Abstract: The EPA regulates ambient particulate matter (PM) because substantial associations have been established between PM and health impacts. Presently, regulatory compliance involves broad control of PM emission sources based on mass concentration rather than chemical composition, although PM toxicity is likely to vary depending upon PM physicochemical properties. The overall objective of this study was to help inform source-specific PM emission control regulations. For the first time, source-oriented PM was collected from the atmosphere in Fresno, CA, onto 38 source/size substrates. Mice were exposed via oropharyngeal aspiration to equivalent mass doses [50 μg] of two size fractions: ultrafine (Dp < 0.17 μm) and submicron fine (0.17 < Dp < 1 μm) during summer and winter seasons. At 24 h post-exposure, cellular and biochemical indicators of pulmonary inflammation were evaluated in the bronchoalveolar lavage fluid. Significant inflammatory responses were elicited by vehicle, regional background, and cooking PM sources that were dependent on season and particle size. This is the first study of source-oriented toxicity of atmospheric PM and supports source-specific emissions control strategies. Highlights: Toxicity of source-oriented PM collected in Fresno, CA, varied by size and season. Vehicle, regional background, and cooking PM sources caused pulmonary inflammation. Source-oriented PM control strategies may be more appropriate than mass-based.